Research on Hispanics benefits the field of management. Issue 6 (5th August 2014) - Aguinis, Herman; Joo, Harry
Abstract : Purpose: – The papers published in this special issue demonstrate that the field of management can make important contributions to the knowledge about Hispanics and Latin Americans (HLAs) in the workplace. The purpose of this paper is to offer an alternative yet complementary perspective that conducting research on HLAs will make important contributions to the field of management. Design/methodology/approach: – Conceptual paper. Findings: – Research on HLAs provides opportunities to develop and use innovative research design and measurement approaches (including qualitative and hybrid methods), leads to innovative solutions and protocols for addressing ethical challenges and Institutional Review Board regulations, and creates opportunities to access large secondary databases, sources of data collection, and research funding. Research limitations/implications: – Additional research is needed to realize the benefits that result from conducting research on HLAs in the workplace. Practical implications: – Because research on HLAs involves designing studies with an end in mind, results will lead to actionable knowledge that will help bridge the science-practice gap. Social implications: – Future research on HLAs is likely to have important social implications given that demographic changes in the USA have catapulted HLAs into soon becoming the largest ethnic minority group in the country and Hispanic workers are projected to represent about 80 percent of the total growth in the US labor force over the next four decades. Originality/value: – The alternative perspective that conducting research on HLAs will benefit the field of management is not meant to compete with but, rather, complement contributions of the other papers published in this special issue.